Infectious Diseases and Nanomedicine II c - Adhikari, Rameshwar; Thapa, Santosh; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2014)
The book addresses the interdisciplinary scientific approach for the systemic understanding of connections between major human diseases and their treatment regime by applying the tools and techniques of nanotechnology. It also highlights the interdisciplinary collaborative researches for innovation in Biomedical Sciences. The book is a second volume which presents collection of best papers presented in the First International Conference on Infectious Diseases and Nanomedicine held during Dec. 15-18, 2012 in Kathmandu, Nepal. The book focuses mainly on the topics: emerging infectious diseases; antimicrobial agents, vaccines and immunity; drug design, drug delivery and tissue engineering; and nanomaterials and biomedical materials.
Bacterial Resistance to Quaternary Ammonium Compounds (QAC) Disinfectants -- Immunological Markers that Correlate with Protection Immunity against Tularemia Infection -- Application of Plant Cell and Tissue Culture for the Production of Phytochemicals in Medicinal Plants -- Microbial Pathogenicity: A New Approach to Drug Development -- Current Trend on Syphilis Diagnosis: Issues and Challenges -- Rapid Spreading and Immune Evasion by Vaccinia Virus -- Nanonization Increases the Antileishmanial Efficacy of Amphotericin B: An Ex-vivo Approach.
Keywords: Chemistry; Medicinal chemistry; Nanochemistry; Infectious diseases; Chemistry; Medicinal Chemistry; Nanochemistry; Infectious Diseases; Electronic books